Performance artivista em Belo Horizonte 2007 - 2015 + a performance Real - Isaque Ribeiro (2017)
This research sought to verify the ways in which the movements of political and social resistance (activist practices) have appropriated aesthetic and creative configurations to diffuse their purposes of contestation, whereas, jointly, aimed to investigate the presence of political and social engagement in contemporary artistic practices. Its goal was to draw a theoretical / practical reflection about the articulation of art / politics starting from the approach of activism practices marked by spectacularity traits, artistic performances linked to everyday life and to the social, that also consider political issues as their manifest subject and / or commitment, as well as daily life events that share similar characteristics to resist social oppression and injustice. The analyses, lastly, aimed to evaluate their ways of aesthetic experimentation and political expression. The dynamization and dissolution of the boundaries between artistic and activists activities, represented by the neologism artivism, were investigated from Performance Studies approach method, having activities performed in the last years (2007 - 2015) in Belo Horizonte as object of study. Through the proposal of the term Artivist Performance, or even, Artivism Performatic, the aim was to weave an analysis that also counted on artistic experiments through the performance named Real